About the Pragmatic of Pronoun 우리 [Uli] in the Advertising Text (on the Material of the Korean Language) - Botirovna, Mukhiddinova Malika (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses the role of personal pronouns on the example of us and their importance to use in advertising texts or in sentence-appeals. Personal pronouns express not only our own position and attitude towards other participants in the conversation, but also reflect the meanings of social and social relations.Inparticular, we can say that this is due to the psycholinguistic aspect of the problem우리 [uli] “we” with linguistic-cognitive and linguistic-cultural aspects. The linguistic-cognitive approach to the description of the pronoun우리[uli] “we” is based on a certain evolution, which was experienced by the interpretation of personal pronouns during the transition from a system-structural to anthropo oriented orientation of the description.